1967
DOI: 10.1037/h0083000
|View full text |Cite
|
Sign up to set email alerts
|

Simple reaction time in schizophrenic, retarded, and normal children under regular and irregular preparatory interval conditions.

Abstract: A reaction-time experiment was carried out as an attempt to replicate, with minor modifications, Rodnick and Shakow's (1940) study, "Set in the schizophrenic as measured by a composite reaction time index." Ss were 20 schizophrenic, 20 retarded, and 20 normal children. The procedure consisted of regular and irregular preparatory interval conditions. The results demonstrated that the schizophrenics were slower and more variable than the control groups. When applying the set-index formulae, a 10 per cent overlap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1972
1972
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Low intellectual functioning, by itself, is unlikely to influence RT appreciably. Previous research has shown only minor elevations in RT level and not exaggerated PI effects in retarded persons (Czudner & Marshall, 1967;Tizard & Venables, 1956). However, the lower, albeit nonsignificant, PPVT scores in the girls, along with their increased offdrug higher negative symptom ratings, may indicate a more severe cognitive dysfunction, some of which at least may have persisted during drug treatment, as suggested in the next paragraph, and influenced RT performance.…”
Section: ~ 4t10-mentioning
confidence: 84%
See 2 more Smart Citations
“…Low intellectual functioning, by itself, is unlikely to influence RT appreciably. Previous research has shown only minor elevations in RT level and not exaggerated PI effects in retarded persons (Czudner & Marshall, 1967;Tizard & Venables, 1956). However, the lower, albeit nonsignificant, PPVT scores in the girls, along with their increased offdrug higher negative symptom ratings, may indicate a more severe cognitive dysfunction, some of which at least may have persisted during drug treatment, as suggested in the next paragraph, and influenced RT performance.…”
Section: ~ 4t10-mentioning
confidence: 84%
“…However, the girls had higher BPRS and SANS scores than the boys when the off-drug ratings were used for all participants, t (13) ≥ 2.17, p < .05 6 Asarnow et al, 1994; Czudner & Marshall, 1967). However, because negative symptoms are indicative of poor prognosis, and poor prognosis in schizophrenia is associated with more impaired information processing (Nuechterlein, 1977; Zahn & Carpenter, 1978), then the data are, to that extent, consistent with previous studies in adult schizophrenia.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Czudner & Marshall (1967) findings indicated that the curves of the regular and the irregular procedures intersected at the 9-second interval. It was also found that there was a statistically significant difference between the regular and the irregular procedure at the 1-, 2-, 4-, and 7.5-second intervals among the normals, while the schizo phrenic subjects' performance indicated no significant difference between the two procedures except at 1-second interval.…”
Section: Theories Of Attentionmentioning
confidence: 99%
“…Given that limbic structures within the temporal lobe have been shown to have attention-directing properties (Bagshaw & Benzies, 1968;Bagshaw, Kimble, & Pribram, 1965), it is possible that temporal lobe dysfunction is responsible for the RT deficit noted in these studies. The crossover is not influenced by IQ or general brain damage (Czudner & Marshall, 1967;Olbrich, 1972;Tizard & Venables, 1956), making variable foreperiod RT a good measure to use with a neurological population.…”
mentioning
confidence: 99%